Optimal Transmission of Gaussian Markov Signal through Noiseless Feedback Channels with Memory; Control and Communications (SIBCON) - Rozhkova S. V. Svetlana Vladimirovna; Rozhkova V. I. Valentina Ivanovna; Lasukov V. V. Vladimir Vasilievich; Devyashina E. V. Elena Vadimovna (2016, 2016)
Title screen